Computer-guided drug repurposing: Identification of trypanocidal activity of clofazimine, benidipine and saquinavir - Bellera, Carolina Leticia (2015)
In spite of remarkable advances in the knowledge on Trypanosoma cruzi biology, no medications to treat Chagas disease have been approved in the last 40 years and almost 8 million people remain infected. Since the public sector and non-profit organizations play a significant role in the research efforts on Chagas disease, it is important to implement research strategies that promote translation of basic research into the clinical practice. Recent international public-private initiatives address the potential of drug repositioning (i.e. finding second or further medical uses for known-medications) which can substantially improve the success at clinical trials and the innovation in the pharmaceutical field. In this work, we present the computer-aided identification of approved drugs clofazimine, benidipine and saquinavir as potential trypanocidal compounds and test their effects at biochemical as much as cellular level on different parasite stages. According to the obtained results, we discuss biopharmaceutical, toxicological and physiopathological criteria applied to decide to move clofazimine and benidipine into preclinical phase, in an acute model of infection. The article illustrates the potential of computer-guided drug repositioning to integrate and optimize drug discovery and preclinical development; it also proposes rational rules to select which among repositioned candidates should advance to investigational drug status and offers a new insight on clofazimine and benidipine as candidate treatments for Chagas disease. One Sentence Summary: We present the computer-guided drug repositioning of three approved drugs as potential new treatments for Chagas disease, integrating computer-aided drug screening and biochemical, cellular and preclinical tests.